Diagnostic Value of Ultrasonography in Patients Suspected Acute Appendicitis - Elahifar, MA; Taheri, H; Bighamian, A (Nepalese Journal of Radiology, 2013)
Introduction: Appendectomy is one of the most frequently performed abdominal operations in surgical practice. Preoperative imaging has been demonstrated to improve diagnostic accuracy in appendicitis. Abdominal ultrasonography (US) is the most commonly and first-line imaging modality used for diagnosing acute appendicitis (AA).The aim of this study was to demonstrate the diagnostic value of abdominal ultrasonography for diagnosing acute appendicitis. Methods: In a retrospective study, we analyzed 200 consecutive patients with abdominal pain that undergoing appendectomy, from June 2009 to April 2012. Patient characteristics, preoperative ultrasonography (US) and laboratory assessment including WBC were collected. Final diagnosis of appendicitis was confirmed by histopathological examination. Results were compared with US. Results: Two hundred patients were admitted to this study that undergoing appendectomy. Mean age was 24 years (range: 1 to 91 years), and 57% were females. Patient White blood cell counts were found to be high in 78% while it was 86% for AA group and 64% for NA group (p < 0.05). One hundred sixty-six of these patients (83%) were diagnosed as acute appendicitis on pathology, and 34 (17%) were diagnosed differently. 157 of patients underwent US, eighty two of this patients diagnosed as acute appendicitis on US examinations and in 78 of them were also reported as acute appendicitis on histopathological examination. The sensitivity and specificity of abdominal US for diagnosing appendicitis were 70% and 90.2% respectively. Positive predictive value (PPV) was 93% and negative predictive value (NPV) was reported 62%. Conclusion: Ultrasonography has a high PPV and specificity, so as a diagnostic tool, positive US strongly suggests the diagnosis of AA. A low negative predictive value recommends that negative US is not sufficient to exclude the diagnosis of AA and patients could not be managed on an outpatient basis following a negative scan. Nepalese Journal of Radiology; Vol. 2; Issue 2; July-Dec. 2012; 13-19 DOI: http://dx.doi.org/10.3126/njr.v2i2.7680